Safety and efficacy of tofacitinib in children with ulcerative colitis complicated with arthropathy: a single-center study - Miao, Shijian; Wang, Shengnan; Hu, Wenhui; Huang, Ying; Shi, Yu (Frontiers in Pediatrics, 2025)
ObjectivesTofacitinib is an oral Janus kinase (JAK) inhibitor initially used for the treatment of arthritis. It demonstrated to effectively induce and maintain remission in adults with inflammatory bowel disease (IBD). However, data on its safety and efficacy in children with ulcerative colitis (UC), particularly in children with comorbid arthropathy, remained limited. This study aimed to evaluate the safety and efficacy of tofacitinib in treating children with UC who also had comorbid arthropathy.MethodsWe conducted a retrospective cohort study enrolling children with UC and comorbid arthropathy who received tofacitinib treatment at the Gastroenterology Department of the Children's Hospital of Fudan University from January 2018 to December 2024. All enrolled UC patients underwent blood tests, stool tests, and colonoscopies, with the Pediatric Ulcerative Colitis Activity Index (PUCAI) used to assess clinical indicators, clinical response, and clinical remission.ResultsA total of 16 patients met the inclusion criteria, all of whom presented with comorbid arthropathy. The mean age at onset was 7.1 ± 3.7 years, with a mean body mass index (BMI) of 14.6 ± 2.0 kg/m2. All patients had previously failed biologic therapy with infliximab. The majority patients initiated tofacitinib treatment at a starting dose of 2.5 mg twice daily (bid) and adjusted based on clinical response, with a maximum dose of 5 mg bid. Fecal calprotectin and endoscopic scores decreased significantly by weeks 14, 21, and 30, while albumin and BMI levels increased (all p < 0.05). The mean PUCAI scores also demonstrated a significant decline. One patient (6.25%) achieved clinical response by week 7, nine (56.25%) by week 14, and five (31.25%) by week 21. Six patients (37.5%) achieved clinical remission by week 30.ConclusionsOur study provided promising evidence for the safety and efficacy of tofacitinib as part of the treatment regimen for children with UC complicated with arthropathy. Further large-scale, prospective studies are needed to confirm these findings.